147k views
1 vote
Choose the best description of the roots of the equation 3x 2 - 4x + 5 = 0.

User Ozgrozer
by
5.5k points

1 Answer

4 votes
For this case we have the following polynomial:

3x ^ 2 - 4x + 5 = 0
Using the resolver we have:

x = (-b +/- √(b^2 - 4ac))/(2a)
Substituting values we have:

x = (-(-4) +/- √((-4)^2 - 4*3*5))/(2*3)

x = (4 +/- √(16 - 60))/(6)

x = (4 +/- √(-44))/(6)

x = (4 +/- √(-4*11))/(6)

x = (4 +/- 2√(-11))/(6)

x = (2 +/- √(-11))/(3)

x = (2 +/- i√(11))/(3)
Answer:
We observe that the solution to the quadratic equation are two imaginary roots.
User Charlie Weems
by
5.4k points